2003
DOI: 10.1002/ajmg.b.20018
|View full text |Cite
|
Sign up to set email alerts
|

Is the α‐2A adrenergic receptor gene (ADRA2A) associated with attention‐deficit/hyperactivity disorder?

Abstract: Attention-Deficit/Hyperactivity Disorder (ADHD) is a complex childhood-onset psychiatric disorder characterized by marked symptoms of inattention, hyperactivity, and impulsivity. The role of genetic factors in its etiology is strongly supported by family, adoption, and twin studies. Although most of the molecular studies have investigated the dopamine D4 receptor gene (DRD4) and the dopamine transporter gene (DAT1) genes in its etiology, pharmacological and brain imaging evidences seem to indicate that genes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
3
6

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(75 citation statements)
references
References 30 publications
(38 reference statements)
1
65
3
6
Order By: Relevance
“…Previous studies implicated the m allele (the rarer G allele) of the MspI marker in the risk for ADHD. 29,30,32,46 We found a trend for association and linkage between the m allele of MspI and ADHD using the TDT (P ¼ 0.13 for ADHD-C and P ¼ 0.086 for ADHD-C þ PI). In contrast, TDT analysis of the DraI RFLP yielded clearly significant results for ADHD-C (P ¼ 0.03) but not for ADHD-PI (P ¼ 0.37), as well as for both subtypes combined (ie, P ¼ 0.028 for ADHD-C þ PI).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Previous studies implicated the m allele (the rarer G allele) of the MspI marker in the risk for ADHD. 29,30,32,46 We found a trend for association and linkage between the m allele of MspI and ADHD using the TDT (P ¼ 0.13 for ADHD-C and P ¼ 0.086 for ADHD-C þ PI). In contrast, TDT analysis of the DraI RFLP yielded clearly significant results for ADHD-C (P ¼ 0.03) but not for ADHD-PI (P ¼ 0.37), as well as for both subtypes combined (ie, P ¼ 0.028 for ADHD-C þ PI).…”
Section: Discussionmentioning
confidence: 68%
“…11 Despite its potential relevance, only a handful of studies have investigated the ADRA2A gene as a potential risk factor for the development of ADHD. [29][30][31][32]46 Those studies analyzed an MspI polymorphism in the promoter of the gene and looked for association with ADHD and/or its symptoms using a variety of statistical approaches. Comings et al found that in Tourette's syndrome patients who also met DSM-IV criteria for ADHD, there was a modest correlation between symptom scores and the MspI polymorphism, but the degree to which that sample represented the complete spectrum of ADHD patients is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibilities that the a 2 -ARs (Roman et al, 2003) or the NE transporters on the presynaptic membranes (Xu et al, 2000) are impaired genetically and that this results in an increase in extracellular NE level in the SPORTS rat hippocampus cannot be excluded; however, the decreased NE in the whole homogenate of SPORTS rat hippocampus prompted us to first examine the activity of MAOA, which is the enzyme catalyzing the degradation of monoamines including NE (Daniel et al, 2001). We found that the enzyme activity of MAOA, but not of MAOB, was decreased in the hippocampus of SPORTS rats.…”
Section: Cumulative Revolution Numbers/12hrmentioning
confidence: 99%
“…The critical roles of ␣ 2A ARs in these physiologic processes has prompted association and family studies of receptor genetic variability to identify potential risk factors or disease modifiers and pharmacogenomic studies to identify potential treatment-response loci for multiple central nervous system, cardiovascular, and metabolic diseases (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). These studies were performed with single restriction fragment-length polymorphisms (RFLPs) of the ␣ 2A AR gene, such as a DraI RFLP, and generally have shown only weak or no associations or a lack of reproducibility.…”
mentioning
confidence: 99%